5G mmWave OTA test technologies - Yunzhi LING; Yu ZHANG; Hu XU; Ting CHEN (Dianxin kexue)
Millimeter wave (mmWave) is one of the key technologies of 5G communication, 5G communication will bring revolutionary improvements in network capacity, data rate, and delay.5G testing has changed from the previous conduction type to OTA testing.The challenges and difficulties encountered in 5G mmWave large bandwidth OTA testing were analyzed, and a variety of OTA test key technologies was put forward, finally the construction of 5G mmWave OTA test platform for a large bandwidth was discussed, the radio performance testing of various devices under millimeter wave OTA was completed.